1990
DOI: 10.1128/jcm.28.4.798-800.1990
|View full text |Cite
|
Sign up to set email alerts
|

Simple assay of calcium dependency for virulent plasmid-bearing clones of Yersinia enterocolitica

Abstract: A simplified procedure to detect the calcium dependency of virulent plasmid-bearing strains of Yersinia enterocolitica was developed. A low-calcium, agarose-based medium of brain heat infusion with added magnesium effectively differentiated plasmid-bearing and plasmidless isolates. Further, the expression of calcium dependency in plasmid-bearing strains of Y. enterocolitica as measured by the average colony diameter was proportional to the calcium concentration of the assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 8 publications
4
39
0
Order By: Relevance
“…SOMMERS corresponding Pcells (2.4 mm in diameter) ( Fig. 2 [ii] B) when grown on BHA at 37C (Table 1) as reported previously (Bhaduri et al 1990), whereas pYV/pCD-bearing colonies (KIM 5) and pYV/pCD-less colonies (Kuma) of Y. pestis were approximately the same size (1.3-1.4 mm; SD Ϯ 0.11) ( Table 1). Colony morphologies of the CV-positive and CV-negative strains of Y. enterocolitica, Y. pseudotuberculosis and Y. pestis were examined further by using a low-magnification stereomicroscope.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…SOMMERS corresponding Pcells (2.4 mm in diameter) ( Fig. 2 [ii] B) when grown on BHA at 37C (Table 1) as reported previously (Bhaduri et al 1990), whereas pYV/pCD-bearing colonies (KIM 5) and pYV/pCD-less colonies (Kuma) of Y. pestis were approximately the same size (1.3-1.4 mm; SD Ϯ 0.11) ( Table 1). Colony morphologies of the CV-positive and CV-negative strains of Y. enterocolitica, Y. pseudotuberculosis and Y. pestis were examined further by using a low-magnification stereomicroscope.…”
supporting
confidence: 63%
“…Brain heart infusion (BHI) broth, BHA and 0.1% peptone water were prepared as recommended by the supplier (Becton-Dickinson, Sparks, MD). Low-calcium (238 mM Ca 2+ ) BHI agarose (BHO) was prepared by adding agarose (GibcoBRL, Grand Island, NY) to final concentration of 1.2% to BHI broth supplemented with 0.1% magnesium chloride (Sigma Chemical Co., St. Louis, MO), and CR (Sigma Chemical Co.) was added to BHO at a concentration of 75 mg/mL to prepare CR-BHO as described previously (Bhaduri et al 1990;Bhaduri et al 1991). Calcium-deficient magnesium oxalate agar (MOX) was prepared by adding 20% D-galactose (Sigma Chemical Co.), 0.25 M sodium oxalate (Sigma Chemical Co.) and 0.25 M magnesium chloride (Sigma Chemical Co.) to tryptic soy agar (Becton-Dickinson) (Bhaduri et al 1990) and CR-MOX was prepared by adding 1% CR to MOX as described previously (Bhaduri et al 1991).…”
Section: Preparation Of Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies (McDermott et al 1993;Goverde et al 1994) have shown that the choice of incubation temperature affects the growth kinetics of plasmid-bearing and plasmid-cured strains of Escherichia coli and Y. enterocolitica. In general, virulence plasmid expression in Yersinia occurs at temperatures > 30 C, this expression is usually observed in phenotypic characteristics such as calcium dependency, autoagglutination and production of outer membrane proteins (Laird and Cavanaugh 1980;Cornelis et al 1987;Bhaduri et al 1990). Goverde et al (1994) reported that virulence plasmid expression at temperatures greater than 30 C retards the growth rate of plasmid-bearing Y. enterocolitica strains as plasmid replication places an additional metabolic burden on growing cells.…”
Section: Introductionmentioning
confidence: 99%